Neo-Taylorism in the Digital Age: Workplace Transformations in French and German Retail Warehouses - Gautié, Jérôme; Jaehrling, Karen; Perez, Coralie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
The paper analyzes how digitalization in conjunction with changes to the economic environment are affecting the nature of low-skilled jobs in the logistics sector; in particular, job content and the working and employment conditions attached to those jobs. On the basis of expert interviews and company case studies in French and German retail warehouses, the authors investigate whether the adaptation of these jobs corresponds to the more general ‘neo-Taylorist’ transformation of workplaces discussed in the literature and seek to identify those factors that are helping to stabilize or modify this trend.Drawing on the comparative labour relations literature, which distinguishes between different types of workers’ power resources (institutional, associational and structural), the study examines how and to what extent employees and their representatives renegotiate or influence techno-organizational choices. By focusing on firms headquartered in France and Germany, we can shed some light on whether the institutional power of organized labour may enable them to foster trajectories other than the kind of ‘digital Taylorism’ we see in liberal market economies.The findings point, however, to a general convergence on digitally enhanced ‘Neo-Taylorism,’ which is characterized by deskilling and intensification of performance control. The limited cross-country variation can largely be explained by the very similar effects across countries of ‘lean’ supply-chain transformation and the trend toward outsourcing and offshoring, which negatively affect workers’ structural power. Moreover, associational resources are negatively affected by the deskilling trend. Meanwhile, the findings provide some evidence of a beneficial impact from the institutional power of worker representatives in both countries: in particular, the rights to veto and co-determine performance management systems. These rights have not altogether helped prevent the shift toward neo-Taylorism but have contributed to somewhat less intense forms of neo-Taylorism.